Peningkatan pemahaman materi rangkaian listrik Untuk Mahasiswa PGSD UMS melalui Media Elektroconnect - Fajarwati, Salsabila; Afifah, Marwa Faridatul; Nisa, Khoirun; Gusmiarni, Siti Rini; Khoiriyah, Hanifatun (Nur Science Institute, 2024)
Electrical circuit material is often considered complex and requires in-depth understanding. This study aims to evaluate the effectiveness of Elektroconnect media in improving UMS PGSD students' understanding of the material. This study uses a classroom action research approach with four main stages, namely planning, action, observation, and reflection. The methods used include quantitative and qualitative approaches, with instruments in the form of pre-test and post-test questions. The results of the study showed an increase in student understanding after using Elektroconnect media, as indicated by a comparison of the pre-test and post-test results. These findings indicate that Elektroconnect media is effective in supporting the learning of electrical circuit material among UMS PGSD students.